Modified Ponseti technique for management of neglected clubfeet. Issue 1 (January 2018) - Mehtani, Anil; Prakash, Jatin; Vijay, Vipul; Kumar, Nishikant; Sinha, Abhinav
Abstract : Achieving adequate dorsiflexion in neglected clubfoot cases remains challenging. On a close observation of the Ponseti method, we have now made certain modifications from the standard Ponseti protocol. This has helped us improve functional results, as well as reduce the number of casts in this walking-age group. From March 2011 onward, we managed 62 neglected clubfeet in 41 patients with the modified protocol. All these patients were treated with serial weekly above-knee casts. The feet were assessed by Dimeglio and Pirani scorings, which were done every week. These children were closely monitored and followed up at regular intervals for any signs of relapses. The mean age group was 3.1 years (1.1–12 years). The mean follow-up period for these feet was 3 years (1.2–4 years). Mean Dimeglio score before treatment was 15.9, and after treatment it was 0.52. Mean Pirani score before treatment was 4.21 and after treatment it was 0.03. The average number of casts before tenotomy with our modified method was 6.9. Percutaneous tenotomy was done in all the cases. The mean dorsiflexion achieved at the end of treatment was 21.3° (15°–40°). Our modified Ponseti technique is a very effective and reproducible method for correction of neglected clubfeet. We feel that an extensive soft tissue surgery may not be required for neglected clubfeet even up to the age of 10 years.